Exploration of different biomasses as graphite cathode precursors for dual-ion batteries - Luo, Hongyi (Transactions on Environment, Energy and Earth Sciences, 2026)
Following lithium batteries, dual-ion batteries have attracted attention for their inherent benefits of affordability, elevated voltage, and environmental sustainability. As a key component of such batteries, the performance characterization of graphite cathode is crucial for their cycle stability. In order to minimize the barrier to anion embedding in the graphite cathode, the electrode material needs to be characterized by a high degree of graphitization as well as a suitable layer spacing. Therefore, this paper compares the properties of five biomass materials used for the fabrication of carbon electrodes, namely coconut shell, ginger root, microcrystalline cellulose, kraft lignin and bamboo, after graphitization from the data point of view of ID/IG values as well as (002) facet spacing. In these five data sets, the best graphitization was in coconut shell but the best layer spacing was in ginger root. And in the comparison of the main components of biomass, cellulose performed better than lignin overall after graphitization. Further, this paper makes conjectures about better results with high cellulose content of general biomass precursors and measures to dissolve feedstock lignin and hemicellulose. In addition, this paper recommends the graphitization of biomass using an iron-cobalt catalyst and carbonization heating conditions above 1300°C.